Priorities for competitiveness in the maquila industruy. Case studies - Sarache Castro, William Ariel; Universidad Nacional de Colombia, Manizales (Pontificia Universidad Javeriana, 2011)
The market demands that industry should define priorities and strategies to satisfy their customers´ needs. This article constructs and applies a multi-criterion procedure for the maquila industry to define priorities from the standpoint of its customers, the major clothing brands in the US market: and it constructs an indicator to determine its position in the maquila market. Finally, it presents the results of a pilot study of 18 Colombian maquila businesses.